Molecular Evolution of GDP-D-Mannose Epimerase (GME), a Key Gene in Plant Ascorbic Acid Biosynthesis - Tao, Junjie; Wu, Han; Li, Zhangyun; Huang, Chunhui; Xu, Xiaobiao (Frontiers in Plant Science, 2018)
The widespread ascorbic acid (AsA) plays a vital role in plant development and abiotic stress tolerance, but AsA concentration varies greatly among different plants. GDP-D-mannose epimerase (GME), which catalyzes GDP-D-mannose to GDP-L-galactose or GDP-L-gulose, is a key enzyme in plant AsA biosynthesis pathway. Functions and expression patterns of GME have been well studied in previous works, however, little information is known about the evolutionary patterns of the gene. In this study, GME gene structure, corresponding conserved protein motifs and evolutionary relationships were systematically analyzed. A total of 111 GME gene sequences were retrieved from 59 plant genomes, which representing almost all the major lineages of Viridiplantae: dicotyledons, monocotyledons, gymnosperms, pteridophytes, bryophytes and chlorophytes. Results showed that homologs of GME were widely present in Viridiplantae. GME gene structures were conservative in higher plants, while varied greatly in the basal subgroups of the phylogeny including lycophytes, bryophytes and chlorophytes, suggesting GME gene structure might have undergone severe differentiation at lower plant and then gradually fixed as plant evolution. The basic motifs of GME were strongly conserved throughout Viridiplantae, suggesting the conserved function of the protein. Molecular evolution analysis showed that strong purifying selection was the predominant force in the evolution of GME. A few branches and sites under episodic diversifying selection were identified and most of the branches located in the subgroup of chlorphytes, indicating episodic diversifying selection at a few branches and sites may play a role in the evolution of GME and diversifying selection may have occurred at the early stage of Viridiplantae. Our results provide novel insights into functional conservation and the evolution of GME.